2019
DOI: 10.1186/s13075-019-2078-5
|View full text |Cite
|
Sign up to set email alerts
|

High risk of gastrointestinal hemorrhage in patients with systemic sclerosis

Abstract: BackgroundSystemic sclerosis (SSc), a life-threatening autoimmune disease characterized by vasculopathy. Numerous SSc patients demonstrate gastrointestinal (GI) involvement but the delicate GI bleeding risk remains sparse. We aimed to explore the role of SSc in determining the long-term risk of GI bleeding, including bleedings of upper (peptic and non-peptic ulcers) and lower GI tracts.MethodsPatients with SSc diagnosis were identified from the Catastrophic Illness Patient Database and the National Health Insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Recently, it was observed that SSc can be an independent risk factor for GI bleeding events with an HR of 2.98 (95%CI: 2.21-4.02)[ 84 ]. GAVE is part of the spectrum of vascular disease in these patients[ 16 , 24 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Recently, it was observed that SSc can be an independent risk factor for GI bleeding events with an HR of 2.98 (95%CI: 2.21-4.02)[ 84 ]. GAVE is part of the spectrum of vascular disease in these patients[ 16 , 24 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The systemic scleroderma further increases the risk for fatal manifestations, including Ogilvie syndrome or intestinal pseudo-obstruction [11]. GI symptoms of 5.3-55.6% of systemic scleroderma patients reportedly increase their risk of malnutrition [12].…”
Section: Gastrointestinal Manifestations In Sclerodermamentioning
confidence: 99%
“…Lifestyle modification is also recommended (avoidance of large and late-night meals) [1,3] . Gastric involvement 50% [10] -Gastroparesis 50% [10] -Gastric Antral Vascular Ectasia (GAVE) 5.6-22.3% [3,10] Gastric Bleeding Ectasis 0.6-0.8% [11] -Upper GI Bleeding 3.2% [12] 1. Gastric emptying study [1,3,9] .…”
Section: Good Oral Hygiene and Artificialmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] The EULAR Scleroderma Trial and Research cohort revealed 6.6% of deaths from SSc that resulted from GI complications among elderly patients and patients with diffuse skin involvement. [ 7 , 9 , 10 ] The affected patients developed a high frequency of GI symptoms at an early stage of systemic scleroderma.…”
Section: Introductionmentioning
confidence: 99%